Geological and geomorphological preconditions for flash floods in Slovakia - BEZÁK, Vladimír; SOTÁK, Ján; BILČÍK, Dušan; BEDNARIK, Martin; MADARÁS, Ján; SOLDÁNOVÁ, Veronika (Contributions to Geophysics and Geodesy, 2023)
In Slovakia, we singled out thirty areas in which flash floods occurred repeatedly. The aim of our analysis was to assess the influence of geological and geomorphological factors on the occurrence of such floods. Two areas were selected as an example of the influence of these factors. It is the area of the upper reaches of Rimavica River and the area of Levočské vrchy Hills. In the first case, the relief appears to be the main factor in the occurrence of sudden floods, in the second one it is mainly the geological composition of the area formed mainly by flysch formations, which make it difficult for intense precipitation to soak in and also encourage the susceptibility of the area to landslides.